Cervical adenocarcinoma in situ: Human papillomavirus types and incidence trends in five states, 2008–2015. Issue 3 (6th May 2019) - Cleveland, Angela A.; Gargano, Julia W.; Park, Ina U.; Griffin, Marie R.; Niccolai, Linda M.; Powell, Melissa; Bennett, Nancy M.; Saadeh, Kayla; Pemmaraju, Manideepthi; Higgins, Kyle; Ehlers, Sara; Scahill, Mary; et al.
Abstract : Primary prevention through the use of human papillomavirus (HPV) vaccination is expected to impact both cervical intraepithelial neoplasia (CIN) and adenocarcinoma in situ (AIS). While CIN is well described, less is known about the epidemiology of AIS, a rare cervical precancer. We identified AIS and CIN grade 3 (CIN3) cases through population‐based surveillance, and analyzed data on HPV types and incidence trends overall, and among women screened for cervical cancer. From 2008 to 2015, 470 AIS and 6, 587 CIN3 cases were identified. The median age of women with AIS was older than those with CIN3 (35 vs . 31 years; p < 0.01). HPV16 was the most frequently detected type in both AIS and CIN3 (57% in AIS; 58% in CIN3), whereas HPV18 was the second most common type in AIS and less common in CIN3 (38% vs . 5%; p < 0.01). AIS lesions were more likely than CIN3 lesions to be positive for high‐risk types targeted by the bivalent and quadrivalent vaccines (HPV16/18, 92% vs . 63%; p < 0.01), and 9‐valent vaccine (HPV16/18/31/33/45/52/58, 95% vs . 87%; p < 0.01). AIS incidence rates decreased significantly in the 21–24 year age group (annual percent change [APC] overall: −22.1%, 95% CI: −33.9 to −8.2; APC among screened: −16.1%, 95% CI: −28.8 to −1.2), but did not decrease significantly in any older age group. This report on the largest number of genotyped AIS cases to date suggests an important opportunity for vaccine prevention of AIS, and is the first to document a decline in AIS incidence rates among young women during the vaccine era. Abstract : What's new? Adenocarcinoma in situ (AIS) is a rare histologic type of cervical precancer. Little is known about the epidemiology of AIS, however, and this information is important in the era of human papillomavirus (HPV) vaccination for cervical cancer prevention. In this study, the authors report on the largest collection of genotyped AIS cases to date from the multisite U.S. population‐based HPV Vaccine Impact Monitoring Project. From 2008 to 2015, 470 AIS cases were documented, compared to 6, 587 cervical intraepithelial neoplasia grade 3 (CIN3) cases. AIS was diagnosed at an older age than CIN3 and was associated most frequently with HPV16 or HPV18. These are the first data on AIS incidence trends in the vaccine era; the authors document a decline in incidence among young women, which may be in part attributable to early vaccine impact.